Relation of Clinical Features with Microbiological Findings in Children of Suspected Pulmonary Tuberculosis - Anand Kumar Bhardwaj; Gurpreet Singh; Kusum Mahajan; Gauri Chauhan; Charu Chandwani (JCDR Research and Publications Pvt. Ltd., 2020)
Introduction: Tuberculosis (TB) is an important cause of morbidity and mortality in children especially in TB endemic settings. In endemic regions of TB, it is a major yet an unrecognised factor for death among children. Children are usually assessed when they present with symptoms or signs associated with TB. The standard tuberculin test can be used as an adjunct in diagnosing TB in children, however definitive proof for lesion being of tuberculous origin is finding of tubercle bacilli. Aim: To determine the association between the clinical features in suspected pulmonary TB with sputum positivity. Materials and Methods: Mantoux test for every child suspected to be suffering from TB was done. X-ray radiography was done and findings were recorded from December 2017 to June 2019. Two sputum samples were collected from every suspected case. One in a sterile specimen cup with a tight-fitting cap was sent for Ziehl-Neelsen staining and the other in a falcon tube was sent for Cartridge Based Nucleic Acid Amplification Test (CBNAAT). The data was analysed using Microsoft SPSS version 26.0 and along with graph pad prism software. Results: Out of 53 subjects, 10 patients (19%) tested positive for acid fast bacilli via Ziehl-Neelsen staining as well as CBNAAT and remaining 43 patients (81%) tested negative. Mantoux test results were not significantly different from the percentage of patients with sputum negativity (93.02%). The percentage of sputum positive patients with cavitations on chest X-ray was 70% which was significantly higher. Conclusion: Females were more likely to suffer from TB disease as compared to the males. Sputum positivity was significantly associated with cavitatory lesion on chest X-ray.